Glue solution, glue solution preparation method and method for manufacturing lead-free medium-Tg copper-clad plate
By using specific composition glue liquids and processes in copper clad plates, the problem of insufficient performance of existing copper clad plates is solved, the heat resistance and glass transition temperature of the material are improved, and the performance needs of the high-end market are met.
Patent Information
- Application Number
- CN202411449435.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-31
AI Technical Summary
The existing copper clad plates have insufficient heat resistance, glass transition temperature, flame retardant properties, mechanical properties and thermal expansion coefficient, which cannot meet the demand of high-end markets. Especially under the development of lead-free and high-density installation technology, the materials are processed. The number of thermal shocks and temperatures are subjected to higher.
The glue solution containing polyurethane modified epoxy resin, brominated epoxy resin, modified phenolic epoxy resin, multifunctional epoxy resin, inorganic filler, curing agent, catalyst and organic solvent is prepared by stirring and homogeneous emulsification. The glue liquid is formed, and then immersed and baked with the copper foil through a vertical glue machine and hot-pressed with the copper foil after being hot-pressed to produce a lead-free Tg copper clad plate with high heat resistance.
有效提升了材料的耐热性、韧性、玻璃化转变温度、阻燃性能和热膨胀系数,使其适应复杂的PCB无铅制程要求,提高了材料的整体性能,符合高端市场的技术指标。
Smart Images

Figure CN119220054A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a copper clad laminate manufacturing technology, and in particular to a glue solution, a glue solution preparation method and a method for manufacturing a lead-free medium Tg (glass transition temperature) copper clad laminate. Background Art
[0002] Copper Clad Laminate (CCL) is the main material for manufacturing printed circuit boards (PCBs), and is therefore an indispensable basic electronic material for any electronic product. With the rapid development of the PCB industry, the market demand for high-performance copper clad laminates is increasing. Since its comprehensive development in the lead-free era, the product's heat resistance, glass transition temperature (Tg) value, thermal expansion coefficient (CTE value), PCB processability and other properties have received special attention. The balanced development of copper clad laminate substrate performance has become an important development trend in the development of new copper clad laminate materials.
[0003] The current demand for electronic products to be light, thin, short, small and digital, miniaturization, multi-function, high performance and high reliability have become the mainstream development direction. Therefore, PCB design is moving towards high multi-layer, fine graphics and high density. The requirements for line width, line spacing, aperture, hole wall and other processes in the PCB industry are also gradually moving towards high integration, high density and high multi-layer. For example, the mainstream high-density interconnect laminate (HDI) requires its micro-via aperture to be less than 6mil, the micro-via ring diameter to be less than 0.35mm, the contact density to be more than 130in / m2, the wiring density to be more than 117in / m2, and the line width / line spacing to be less than 0.1mm / 0.1mm. High-level HDI (more than twelve layers) needs to withstand special processes such as high-level multiple hot pressing and more precise and detailed process requirements. With the development of high-density mounting technology, especially the full implementation of lead-free and the rapid development of surface mount technology (SMT), the number of times and temperatures that materials are repeatedly subjected to thermal shock during PCB processing and installation of complete machine accessories are higher than traditional requirements. All of this ultimately translates into a huge challenge to the reliability of high-performance copper clad laminates.
[0004] The existing copper clad laminates have poor overall performance and insufficient heat resistance, which makes them unable to meet the needs of the high-end market. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a glue having good heat resistance, toughness, glass transition temperature, flame retardancy, mechanical properties, heat shock resistance and thermal expansion coefficient.
[0006] In order to solve the above technical problems, the glue provided by the present invention comprises the following components in parts by weight: 30-50 parts of polyurethane modified epoxy resin, 60-80 parts of brominated epoxy resin, 30-50 parts of modified phenolic epoxy resin, 30-50 parts of multifunctional epoxy resin, 30-60 parts of inorganic filler, 5-10 parts of curing agent, 0.5-5 parts of catalyst, 3-8 parts of auxiliary agent and 50-80 parts of organic solvent.
[0007] Preferably, the adhesive contains the following components in parts by weight: 30 parts of polyurethane modified epoxy resin, 60 parts of brominated epoxy resin, 45 parts of modified phenolic epoxy resin, 30 parts of multifunctional epoxy resin, 55 parts of inorganic filler, 8 parts of curing agent, 1.5 parts of catalyst, 3 parts of auxiliary agent and 60 parts of organic solvent.
[0008] Preferably, the adhesive contains the following components in parts by weight: 40 parts of polyurethane modified epoxy resin, 65 parts of brominated epoxy resin, 30 parts of modified phenolic epoxy resin, 35 parts of multifunctional epoxy resin, 40 parts of inorganic filler, 8 parts of curing agent, 0.9 parts of catalyst, 4 parts of auxiliary agent and 70 parts of organic solvent.
[0009] Preferably, the adhesive comprises the following components in parts by weight: 45 parts of polyurethane modified epoxy resin, 60 parts of brominated epoxy resin, 40 parts of modified phenolic epoxy resin, 30 parts of multifunctional epoxy resin, 55 parts of inorganic filler, 7 parts of curing agent, 1.2 parts of catalyst, 5 parts of auxiliary agent and 65 parts of organic solvent.
[0010] Preferably, the organic solvent is a mixture of any one or more of DMF, acetone, butanone, methyl butanone, cyclohexanone, propylene glycol methyl ether, toluene, xylene, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, methanol, isopropanol, propylene oxide, and cyclohexane;
[0011] The brominated epoxy resin includes any one or more of brominated bisphenol A epoxy resin, brominated novolac epoxy resin, and dibromopentaneerythroid epoxy resin;
[0012] The modified novolac epoxy resin is a mixture of any one or more of bisphenol A novolac epoxy resin, o-cresol novolac epoxy resin, and BPA novolac epoxy resin;
[0013] The multifunctional epoxy resin is a mixture of any one or more of a trifunctional epoxy resin and a tetrafunctional epoxy resin;
[0014] The inorganic filler is a mixture of two or more of silicon micropowder, aluminum oxide, zinc oxide, magnesium hydroxide, aluminum hydroxide, barium sulfate, silicon nitride, boron nitride, and talc;
[0015] The inorganic filler is two or more of silicon powder, aluminum oxide, zinc oxide, magnesium hydroxide, aluminum hydroxide, barium sulfate, silicon nitride, boron nitride and talc;
[0016] The auxiliary agent is a mixture of any one or more of an organic silane coupling agent, a titanate ester, and an aluminate coupling agent;
[0017] The curing agent is a mixture of any one or more of 4,4'-dioxydiphenyl sulfone (DDS), dicyandiamide, and phosphorus-containing phenolic curing agent;
[0018] The catalyst is a mixture of any one or more of imidazole, 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-ethyl-4-phenylimidazole and boric acid.
[0019] In order to solve the above technical problems, the present invention provides a method for preparing the glue solution, comprising the following steps:
[0020] S1. Stir the organic solvent, polyurethane-modified epoxy resin, brominated epoxy resin, modified phenolic epoxy resin and multifunctional epoxy resin for 2-3 hours until the epoxy resin is completely dissolved in the organic solvent;
[0021] S2. Add inorganic fillers and additives, and homogenize and emulsify them for 2-4 hours through a homogenizer to fully disperse the inorganic fillers into the resin solution;
[0022] S3. Add curing agent and catalyst, and stir in a cycle for 2-3 hours to obtain the adhesive solution.
[0023] The method for manufacturing a lead-free medium Tg copper-clad laminate using the glue solution comprises the following steps:
[0024] 1. The glue is impregnated on the electronic grade glass fiber cloth through a vertical glue applicator and then baked at a high temperature of 100-200°C for 8-15 minutes to form a continuous prepreg;
[0025] 2. Cover the upper and lower surfaces of the obtained prepreg with copper foil, and heat-press it with a hot press to obtain a high heat-resistant lead-free medium Tg copper-clad laminate.
[0026] The adhesive of the present invention can effectively improve the heat resistance and toughness of the material by adding polyurethane modified epoxy resin, so that the material performance can adapt to the complex and demanding PCB lead-free process requirements; at the same time, mixed modified resins such as brominated epoxy resin, modified phenolic epoxy resin, and multifunctional epoxy resin can better improve the glass transition temperature, flame retardant properties, and mechanical properties of the material. Adding inorganic fillers can further improve the heat shock resistance and thermal expansion coefficient of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solution of the present invention, the following briefly introduces the drawings required for use in the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 It is a flow chart of an embodiment of a method for preparing glue solution of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The words "first", "second" and similar terms used in this application do not indicate any order, quantity or importance, but are only used to distinguish different components. Words such as "include" or "comprises" and similar terms mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. Words such as "connect" or "connected" and similar terms are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect. "Up", "down", "left", "right", "front", "back" and the like are only used to indicate relative position relationships. When the absolute position of the object being described changes, the relative position relationship may also change accordingly.
[0031] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0032] Embodiment 1
[0033] A glue solution comprises the following components in parts by weight: 30-50 parts of polyurethane modified epoxy resin, 60-80 parts of brominated epoxy resin, 30-50 parts of modified phenolic epoxy resin, 30-50 parts of multifunctional epoxy resin, 30-60 parts of inorganic filler, 5-10 parts of curing agent, 0.5-5 parts of catalyst, 3-8 parts of auxiliary agent and 50-80 parts of organic solvent.
[0034] Experimental Example 1, the adhesive contains the following components in parts by weight: 30 parts of polyurethane modified epoxy resin, 60 parts of brominated epoxy resin, 45 parts of modified phenolic epoxy resin, 30 parts of multifunctional epoxy resin, 55 parts of inorganic filler, 8 parts of curing agent, 1.5 parts of catalyst, 3 parts of auxiliary agent and 60 parts of organic solvent.
[0035] Experimental Example 2, the adhesive contains the following components in parts by weight: 40 parts of polyurethane modified epoxy resin, 65 parts of brominated epoxy resin, 30 parts of modified phenolic epoxy resin, 35 parts of multifunctional epoxy resin, 40 parts of inorganic filler, 8 parts of curing agent, 0.9 parts of catalyst, 4 parts of auxiliary agent and 70 parts of organic solvent.
[0036] Experimental Example 3, the adhesive contains the following components in parts by weight: 45 parts of polyurethane modified epoxy resin, 60 parts of brominated epoxy resin, 40 parts of modified phenolic epoxy resin, 30 parts of multifunctional epoxy resin, 55 parts of inorganic filler, 7 parts of curing agent, 1.2 parts of catalyst, 5 parts of auxiliary agent and 65 parts of organic solvent.
[0037] An existing glue solution contains the following components in parts by weight: 50 parts of brominated epoxy resin, 45 parts of modified phenolic epoxy resin, 35 parts of multifunctional epoxy resin, 40 parts of inorganic filler, 5 parts of curing agent, 0.8 parts of catalyst, 5 parts of auxiliary agent and 60 parts of organic solvent.
[0038] The performance comparison between the above three experimental examples and the existing glue solution is shown in the following table:
[0039]
[0040]
[0041] The glue of Example 1 can effectively improve the heat resistance and toughness of the material by adding polyurethane modified epoxy resin, so that the material performance can adapt to the complex and demanding PCB lead-free process requirements; at the same time, mixed modified resins such as brominated epoxy resin, modified phenolic epoxy resin, and multifunctional epoxy resin can better improve the material's glass transition temperature, flame retardant properties, and mechanical properties. Adding inorganic fillers can further improve the material's heat shock resistance and thermal expansion coefficient.
[0042] Embodiment 2
[0043] Based on the glue of Example 1, the organic solvent is a mixture of any one or more of DMF, acetone, butanone, methyl butanone, cyclohexanone, propylene glycol methyl ether, toluene, xylene, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, methanol, isopropanol, propylene oxide, and cyclohexane.
[0044] Preferably, the brominated epoxy resin includes any one or more of brominated bisphenol A epoxy resin, brominated novolac epoxy resin, dibromopentaneerythroid epoxy resin, and the like.
[0045] Preferably, the modified novolac epoxy resin is a mixture of any one or more of bisphenol A novolac epoxy resin, o-cresol novolac epoxy resin, and BPA novolac epoxy resin.
[0046] Preferably, the multifunctional epoxy resin is a mixture of any one or more of a trifunctional epoxy resin and a tetrafunctional epoxy resin.
[0047] Preferably, the inorganic filler is a mixture of two or more of silicon micropowder, aluminum oxide, zinc oxide, magnesium hydroxide, aluminum hydroxide, barium sulfate, silicon nitride, boron nitride and talc.
[0048] Preferably, the inorganic filler is two or more of silicon powder, aluminum oxide, zinc oxide, magnesium hydroxide, aluminum hydroxide, barium sulfate, silicon nitride, boron nitride and talc.
[0049] Preferably, the auxiliary agent is a mixture of any one or more of an organic silane coupling agent, a titanate ester, and an aluminate ester coupling agent.
[0050] Preferably, the curing agent is a mixture of any one or more of 4,4'-dioxydiphenyl sulfone (DDS), dicyandiamide, and phosphorus-containing phenolic curing agent.
[0051] Preferably, the catalyst is a mixture of any one or more of imidazole, 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-ethyl-4-phenylimidazole and boric acid.
[0052] Embodiment 3
[0053] The method for preparing the glue solution of embodiment 1 or 2 comprises the following steps:
[0054] S1. Stir the organic solvent, polyurethane-modified epoxy resin, brominated epoxy resin, modified phenolic epoxy resin, and multifunctional epoxy resin for 2-3 hours until the epoxy resin is completely dissolved in the organic solvent;
[0055] S2. Add inorganic fillers and additives, and homogenize and emulsify them for 2-4 hours through a homogenizer to fully disperse the inorganic fillers into the resin solution;
[0056] S3. Add curing agent and catalyst, and stir in a cycle for 2-3 hours to obtain the adhesive solution.
[0057] Embodiment 4
[0058] The method for manufacturing a lead-free medium Tg copper-clad laminate using the glue of embodiment 1 or 2 comprises the following steps:
[0059] 1. The glue is impregnated on the electronic grade glass fiber cloth through a vertical glue applicator and then baked at a high temperature of 100-200°C for 8-15 minutes to form a continuous prepreg;
[0060] 2. The upper and lower surfaces of the obtained semi-cured sheet are covered with copper foil, and hot-pressed by a hot press to obtain a high heat-resistant lead-free medium Tg copper-clad laminate.
[0061] The lead-free medium Tg copper clad laminate manufactured by the method of Example 4 has a material Tg ≥ 150°C, excellent copper foil peel strength, low CTE value, excellent dimensional stability, excellent CAF resistance, UV Blocking and AOI compatibility, low water absorption, and is suitable for the process requirements of PCB lead-free process. The product meets the technical indicator requirements of IPC specifications and is mainly used in consumer electronics, instrumentation, communication equipment, automotive electronics and other fields.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A glue solution, characterized in that: The invention comprises the following components in parts by weight: 30-50 parts of polyurethane modified epoxy resin, 60-80 parts of brominated epoxy resin, 30-50 parts of modified phenolic epoxy resin, 30-50 parts of multifunctional epoxy resin, 30-60 parts of inorganic filler, 5-10 parts of curing agent, 0.5-5 parts of catalyst, 3-8 parts of auxiliary agent and 50-80 parts of organic solvent.
2. The glue solution according to claim 1, characterized in that: The adhesive solution contains the following components in parts by weight: 30 parts of polyurethane modified epoxy resin, 60 parts of brominated epoxy resin, 45 parts of modified phenolic epoxy resin, 30 parts of multifunctional epoxy resin, 55 parts of inorganic filler, 8 parts of curing agent, 1.5 parts of catalyst, 3 parts of auxiliary agent and 60 parts of organic solvent.
3. The glue solution according to claim 1, characterized in that: The adhesive solution contains the following components in parts by weight: 40 parts of polyurethane modified epoxy resin, 65 parts of brominated epoxy resin, 30 parts of modified phenolic epoxy resin, 35 parts of multifunctional epoxy resin, 40 parts of inorganic filler, 8 parts of curing agent, 0.9 parts of catalyst, 4 parts of auxiliary agent and 70 parts of organic solvent.
4. The glue solution according to claim 1, characterized in that: The adhesive contains the following components in parts by weight: 45 parts of polyurethane modified epoxy resin, 60 parts of brominated epoxy resin, 40 parts of modified phenolic epoxy resin, 30 parts of multifunctional epoxy resin, 55 parts of inorganic filler, 7 parts of curing agent, 1.2 parts of catalyst, 5 parts of auxiliary agent and 65 parts of organic solvent.
5. The glue solution according to claim 1, characterized in that: The organic solvent is a mixture of any one or more of DMF, acetone, butanone, methyl butanone, cyclohexanone, propylene glycol methyl ether, toluene, xylene, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, methanol, isopropanol, propylene oxide, and cyclohexane; The brominated epoxy resin includes any one or more of brominated bisphenol A epoxy resin, brominated novolac epoxy resin, and dibromopentaneerythroid epoxy resin; The modified novolac epoxy resin is a mixture of any one or more of bisphenol A novolac epoxy resin, o-cresol novolac epoxy resin, and BPA novolac epoxy resin; The multifunctional epoxy resin is a mixture of any one or more of a trifunctional epoxy resin and a tetrafunctional epoxy resin; The inorganic filler is a mixture of two or more of silicon micropowder, aluminum oxide, zinc oxide, magnesium hydroxide, aluminum hydroxide, barium sulfate, silicon nitride, boron nitride, and talc; The inorganic filler is two or more of silicon powder, aluminum oxide, zinc oxide, magnesium hydroxide, aluminum hydroxide, barium sulfate, silicon nitride, boron nitride and talc; The auxiliary agent is a mixture of any one or more of an organic silane coupling agent, a titanate ester, and an aluminate coupling agent; The curing agent is a mixture of any one or more of 4,4'-dioxydiphenyl sulfone (DDS), dicyandiamide, and phosphorus-containing phenolic curing agent; The catalyst is a mixture of any one or more of imidazole, 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-ethyl-4-phenylimidazole and boric acid.
6. The method for preparing the glue according to any one of claims 1 to 5, comprising the following steps: S1. Stir the organic solvent, polyurethane-modified epoxy resin, brominated epoxy resin, modified phenolic epoxy resin and multifunctional epoxy resin for 2-3 hours until the epoxy resin is completely dissolved in the organic solvent; S2. Add inorganic fillers and additives, and homogenize and emulsify them for 2-4 hours through a homogenizer to fully disperse the inorganic fillers into the resin solution; S3. Add curing agent and catalyst, and stir in a cycle for 2-3 hours to obtain the adhesive solution.
7. A method for manufacturing a lead-free medium Tg copper-clad laminate using the glue solution according to claim 1, comprising the following steps:
1. The glue is impregnated on the electronic grade glass fiber cloth through a vertical glue applicator and then baked at a high temperature of 100-200°C for 8-15 minutes to form a continuous prepreg; 2. The upper and lower surfaces of the obtained semi-cured sheet are covered with copper foil, and hot-pressed by a hot press to obtain a high heat-resistant lead-free medium Tg copper-clad laminate.
